Краевые задачи для стационарных уравнений Гамильтона—Якоби и Беллмана - Маслов, В.П.; Самборский, С.Н. (Український математичний журнал, 1997)
Внодяться розв'язки граничних задач для стаціонарних рівнянь Гамільтона-Якобі та Беллмапа и функціональних просторах (семімодулях) зі спеціальною алгебраїчною структурою, яка відповідає цим задачам. В означених просторах одержані представлення розв'язків через „базисні", а також теорема про їх апроксимацію при апроксимації негладких гамільтоніанів гладкими. Підхід являє собою альтернативу принципу максимума. We introduce solutions of boundary-value problems for the stationary Hamilton-Jacobi and Bellman equations in functional spaces (semimodules) with a special algebraic structure adapted to these problems. In these spaces, we obtain representations of solutions in terms of “basic” ones and prove a theorem on approximation of these solutions in the case where nonsmooth Hamiltonians are approximated by smooth Hamiltonians. This approach is an alternative to the maximum principle.